Perangkat Lunak 3D Modelling Properti sebagai Media Pemasaran menggunakan Augmented Reality Berbasis Android pada Perumahan Graha Cipta Hertasning - Nurkhalik Wahdanial Asbara (STMIK AKBA, 2021)
This study aims to produce an application that can display a 3D house model in an Augmented Reality environment so that it can help buyers to physically see the house they are going to buy as well as to help property company marketing to manage the house by displaying information on house specifications. The result of the research is an application that can display 3D house images and 3D house plans when highlighting the marker in the direction of the highlighted brochure marker object. The method used in making AR applications is Superimposition Based Augmented Reality .The System Testing Method uses a direct test method based on the Black Box technique by testing the functionality of the application, buttons and the suitability of the application results. Keyword : Augmented Reality, House, Marketing